A new model for diffusion bonding and its application to duplex alloys - Orhan, N; Aksoy, M; Eroglu, M (Elsevier Science Sa, 1999)
Diffusion bonding is an advanced bonding process in which two materials, similar or dissimilar, can be bended in solid state. This provides to bond materials in a wide range from low carbon steels to ceramics and composites which cannot be bonded with conventional welding methods. One of the major advantages of this method is to produce new bimetal or dissimilar material couples. The process is diffusion-based and occurs in solid state and because of its increasing use as a commercial process. The estimation of final bonding time is very important but difficult without experiments for many materials. In this study, therefore, a new mathematical model is presented to predict the final bonding time for a sound bonding interface prior to bonding practice. Being different from the previous models, this model assumes a new surface morphology as a sine wave and a new creep mechanism for duplex alloys. The mechanisms operating during diffusion bonding are based on those in pressure sintering studies but here mass transfer by evaporation has been ignored. The driving forces and rate terms for those mechanisms have been altered to reflect the difference of the geometries of the two processes. Also the effect of grain size has been included in the model in case of joining fine-grained materials. In determining diffusion coefficients for duplex alloys, Darken's equation for binary alloys has been used. Depending on this new approach, it was shown that a more realistic final bonding time could be predicted for duplex alloys by comparing the results from this new model with those from the previous ones. As a result, it was determined that the new model could be used in order to estimate the final bonding time of the duplex alloys for a sound bond interface and the relationships between its parameters safely. The predictions from this new model show a very good agreement between practice and theory. (C) 1999 Published by Elsevier Science S.A. All rights reserved.
Keywords: diffusion bonding; bonding time; duplex alloys; creep